Additional information on the birds from Sierra Norte, Guerrero, Mexico. - Almazán-Núñez, R. Carlos (Instituto de Ecología, A.C., 2009)
A systematic list of birds recently observed at the Sierra Norte, Guerrero, Mexico is presented. The information was gathered during field work carried out from July 2001 to September 2002 and October 2007. 101 species belonging in 13 orders and 34 families were observed. I reported 21 additional records for the avifauna of the Sierra Norte, of which some species have been previously mentioned for this region, but there is not confirmation of its presence with precise dates and localities. The Sierra Norte richness increased to 175 species of birds; however, the magnitude of species increment suggests the necessity of more inventories for a more precise knowledge on species’ distribution.